Control of Zoonotic Rabies Disease by Providing Rabies Vaccine To Pets in Sario Tumpaan District, Manado City - Albert Jootje Podung; Geertruida J. V. Assa; Evacuree Svetlana Tangkere (Asia Pacific Journal of Interdisciplinary Studies, 2025)
Cases of zoonotic rabies in Manado City throughout 2018 - 2022 amounted to 11 cases.  The highest cases occurred in 2018 with 6 cases, and every year there are cases of Rabies.  Most of these cases occur due to bites from pets, whether dogs or cats.  In the world, this case often affects children. Some cases of bites can cause death due to severe bite wounds and poor wound management. Community Service Program regarding public awareness of Rabies and Rabies vaccination in pets.  This program will carry out socialization on the importance of Rabies vaccination and Rabies injections for dogs and cats in the Sario Tumpaan Village area, Manado City.  This program will carry out socialization on the importance of Rabies vaccination and Rabies injections for dogs and cats in the Sario Tumpaan Village area, Manado City. The method used in this program is by vaccinating pets against Rabies and providing education on the dangers of Rabies and protecting pets against the Rabies virus. The Rabies vaccination program succeeded in inoculating 32 pets, consisting of 28 dogs and 4 cats.  There were 3 dogs that had been vaccinated and 25 dogs had never been vaccinated.  The age of the animals most frequently vaccinated was 9 animals (28%) under 1 year old; and the least number was 7 animals (22%) aged 1 – 2 years.  The results of the Rabies vaccination still do not cover the majority of the pet population in Sario Tumpaan Village, but are enough to protect the surrounding pet groups.  Thus, community protection against the zoonotic disease Rabies is quite high.